Inducing formation of a corrugated, white-light emitting 2D lead-bromide perovskite via subtle changes in templating cation - Febriansyah, Benny (2020)
Of a series of new 2D lead-bromide perovskites, templated by closely related dications 1–5, a corrugated (110)-oriented structure was attained only in one, 1[PbBr4]. The others display (100) structures. Upon excitation by UV-light, 1[PbBr4] exhibits intrinsic white-light emission that is “colder” than previously reported for this class of compounds.